Micro‐evolutionary diversification among Indian Ocean parrots: temporal and spatial changes in phylogenetic diversity as a consequence of extinction and invasion. (13th May 2015) - Jackson, Hazel; Jones, Carl G.; Agapow, Paul‐Michael; Tatayah, Vikash; Groombridge, Jim J.
Abstract : Almost 90% of global bird extinctions have occurred on islands. The loss of endemic species from island systems can dramatically alter evolutionary trajectories of insular species biodiversity, resulting in a loss of evolutionary diversity important for species adaptation to changing environments. The Western Indian Ocean islands have been the scene of evolution for a large number of endemic parrots. Since their discovery in the 16th century, many of these parrots have become extinct or have declined in numbers. Alongside the extinction of species, a number of the Indian Ocean islands have experienced colonization by highly invasive parrots, such as the Ring‐necked Parakeet Psittacula krameri . Such extinctions and invasions can, on an evolutionary timescale, drive changes in species composition, genetic diversity and turnover in phylogenetic diversity, all of which can have important impacts on species potential for adaptation to changing environmental and climatic conditions. Using mtDNA cytochrome b data, we resolve the taxonomic placement of three extinct Indian Ocean parrots: the Rodrigues Psittacula exsul, Seychelles Psittacula wardi and Reunion Parakeets Psittacula eques . This case study quantifies how the extinction of these species has resulted in lost historical endemic phylogenetic diversity and reduced levels of species richness, and illustrates how it is being replaced by non‐endemic invasive forms such as the Ring‐necked Parakeet. Finally, we use our phylogenetic framework to identify and recommend a number of phylogenetically appropriate ecological replacements for the extinct parrots. Such replacements may be introduced once invasive forms have been cleared, to rejuvenate ecosystem function and restore lost phylogenetic diversity.